THE ROLE OF THE POLYMORPHIC LOCUS ILE157THR OF THE CHEK2 GENE IN THE DEVELOPMENT OF PROSTATE CANCER (Eureka Journal of Health Sciences & Medical Innovation, 2026)
The aim of the study was to investigate the influence of the Ile157Thr polymorphic locus of the CHEK2 gene on the development of prostate cancer. Materials and Methods. The study included a total of 197 blood samples, 90 of which were randomly selected from apparently healthy men aged 45–72 years, 42 from patients with benign prostatic hyperplasia, and 65 from patients with prostate cancer. All samples were obtained from residents of the Andijan region. The resulting blood samples were tested for the presence of the Ile157Thr polymorphism of the СHEK2 gene using allele-specific PCR in the clinical laboratory of the Republican Specialized Scientific and Practical Medical Center of Hematology. The obtained results were analyzed in accordance with the Hardy-Weinberg equilibrium.
Keywords: prostate cancer screening, CHEK2 gene Ile157Thr polymorphism, prostate cancer development, aggressive prostate cancer